A Digital Student Enrollment and Registration System: Design, Implementation, and Database Integration Using Python and SQLite (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Manual student enrollment and registration processes in educational institutions are often time-consuming, prone to errors, and inefficient. This study developed a Digital Student Enrollment and Registration System using Python and SQLite to automate student record management and course registration. The system allows administrators to add, view, update, delete, and search student records, as well as manage enrolled subjects in a structured database. The application uses Object-Oriented Programming (OOP) principles and a command-line interface for ease of operation. Functional testing demonstrated that the system successfully performed all core operations, maintained data integrity, and minimized clerical errors. By implementing database integration, the system ensures permanent storage, reliable retrieval, and organized management of student enrollment information. The study demonstrates how digital systems can improve administrative efficiency and enhance the overall enrollment experience for both students and registrar personnel.